Hybrid woven carbon-Dyneema composites under drop-weight and steel ball impact. (15th March 2020) - Zhao, Y.; Cao, M.; Tan, H.X.; Ridha, M.; Tay, T.E.
Abstract: In this study, the impact behavior and damage mechanism of novel carbon-Dyneema hybrid fabric reinforced plastic composites are investigated using drop-weight and steel ball impact tests. The force-displacement response, energy absorption and damage mechanisms of the hybrid composite were analyzed and compared with those of woven carbon laminates. The experimental results suggest that the impact resistance of the hybrid composites has been improved when benchmarked with carbon fiber composites. The Dyneema fibers suppress the splitting of bottom surfaces during impact but are susceptible to buckling due to the low compressive strength of Dyneema fibers. A multi-scale approach is proposed for modelling impact damage of hybrid woven composite accounting for the interweave patterns. A meso-scale representative volume element of the interwoven hybrid structure is analyzed and discretized into several sub-sections, each regarded as a type of laminate. Then, a macro-scale impact model is established based on the homogenized effective properties of the sub-sections using continuum shell elements. The failure of the material is modelled using energy-based continuum damage mechanics. Overall, the numerical simulations show good agreement with experimental data in terms of impact force history and damage features, providing insight into the impact damage behavior of hybrid composites.